110k views
4 votes
5n + 3 = 2(n + 2) + 3n
N= ???
-Show All Work!-

User Dnul
by
5.9k points

1 Answer

3 votes
Simplifying
5n + 3 = 2(n + 2) + 3n

Reorder the terms:
3 + 5n = 2(n + 2) + 3n

Reorder the terms:
3 + 5n = 2(2 + n) + 3n
3 + 5n = (2 * 2 + n * 2) + 3n
3 + 5n = (4 + 2n) + 3n

Combine like terms: 2n + 3n = 5n
3 + 5n = 4 + 5n

Add '-5n' to each side of the equation.
3 + 5n + -5n = 4 + 5n + -5n

Combine like terms: 5n + -5n = 0
3 + 0 = 4 + 5n + -5n
3 = 4 + 5n + -5n

Combine like terms: 5n + -5n = 0
3 = 4 + 0
3 = 4

Solving
3 = 4
The left and right sides are not equal, therefore there is no solution.
User Andreas Argelius
by
5.8k points